A Genotype-Phenotype Analysis of Glutathione Peroxidase 4 in Human Atrial Myocardium and Its Association with Postoperative Atrial Fibrillation - Islam A. Berdaweel; Alexander A. Hart; Andrew J. Jatis; Nathan Karlan; Shahab A. Akhter; Marie E. Gaine; Ryan M. Smith; Ethan J. Anderson (MDPI AG, 2022)
Heterogeneity in the incidence of postoperative atrial fibrillation (POAF) following heart surgery implies that underlying genetic and/or physiological factors impart a higher risk of this complication to certain patients. Glutathione peroxidase-4 (GPx4) is a vital selenoenzyme responsible for neutralizing lipid peroxides, mediators of oxidative stress known to contribute to postoperative arrhythmogenesis. Here, we sought to determine whether GPX4 single nucleotide variants are associated with POAF, and whether any of these variants are linked with altered GPX4 enzyme content or activity in myocardial tissue. Sequencing analysis was performed across the GPX4 coding region within chromosome 19 from a cohort of patients (N = 189) undergoing elective coronary artery bypass graft (−/+ valve) surgery. GPx4 enzyme content and activity were also analyzed in matching samples of atrial myocardium from these patients. Incidence of POAF was 25% in this cohort. Five GPX4 variants were associated with POAF risk (permutated p ≤ 0.05), and eight variants associated with altered myocardial GPx4 content and activity (p < 0.05). One of these variants (rs713041) is a well-known modifier of cardiovascular disease risk. Collectively, these findings suggest GPX4 variants are potential risk modifiers and/or predictors of POAF. Moreover, they illustrate a genotype-phenotype link with this selenoenzyme, which will inform future mechanistic studies.